Surgical Excision of the Lumbar Disc Herniation in Elementary School Age - Kim, Youn-Soo (Korean Society of Spine Surgery, 2009)
STUDY DESIGN: A retrospective study. PURPOSE: To assess the radiological, clinical features and surgical outcomes of six patients of elementary school age with lumbar disc herniation (LDH). OVERVIEW OF LITERATURE: LDH is common in people in their fourth and fifth decades. However, the condition is extremely rare in children of elementary school age. Moreover, the clinical symptoms and treatments are different from those of adults. METHODS: We reviewed a series of 6 patients under the age of 12 years, who underwent surgery for LDH at our institution between 1992-2002. Initially, all patients were treated conservatively. The indications for surgery were failure of conservative treatment for 3 months, intractable pain and/or progressive neurological impairment. RESULTS: The surgical findings revealed a protruding disc in five cases and a ruptured disc in one. In addition, separation of the vertebral ring apophysis was observed in 3 cases. The symptoms had disappeared completely at the last follow-up. At the last follow-up, the Japanese Orthopaedic Association score was 10 points in 5 cases and 9 points in 1, and the Kirkaldy-Willis criteria was excellent in all patients. No intervertebral disc space narrowing was observed in any patient at last follow up. In addition, there were no degenerative changes in the vertebral endplate and facet joint. CONCLUSIONS: Patients with symptoms that persist for more than 3 months or those with a progressive neurological deficit must be considered for surgical discectomy.